Effect of plant density, spatial arrangement and plant type on weed control in cowpea and soybean: Conference Conference Proceedings of a conference held at the IITA, Ibadan, Nigeria, July 37, 1978 - Nangju, D. (1980)
Since herbicides are not widely used in cowpea and soybean at the present time, cultural and manual methods are important means of weed control in the tropics. Field experiments were conducted at Ibadan (in western Nigeria) to evaluate the effect of plant density, spatial arrangement and plant type on weed control in cowpea (Vigna unguiculata) and soybean. On the average, weeds reduced seed yield of cowpea by about 46% and of soybean by about 34%. In addition, weeds present during pod ripening of soybean significantly reduced the percentage of smooth, clean seed and germination of soybean when maturation occurred during wet weather. Increasing the plant density or reducing row spacing at a given density reduced weed weight and yield loss in soybean. Some cowpea and soybean cultivars were more competitive against weeds than others. Plant characters associated with the competitive ability against weeds were (1) plant height, (2) leaf shape and size and (3) leaf area index. Weed weight was negatively correlated with leaf area index.